The Moderating Effect of Attachment Styles (Anxiety And Avoidance) on Consumer Intention - Vieira, Valter Afonso (2016)
This paper investigates firm-focused customer attachment styles relationship, rather than general or interpersonal attachment styles. We proposed a theoretical framework and analyzed the customers attachment styles and their moderating effect on happiness, commitment, loyalty, satisfaction and preference for closeness. In Study 1, we survey clients from main banks in Brazil, who evaluated their relationship with banks. In Study 2, we survey clients from insurance agent broker. The results showed that the anxiety avoidance interaction had negative association with switching intention. Second, the outcomes suggested that the anxiety avoidance interaction attenuates the main effect of all marketing variables on repurchase intention and switching intention, creating a three-way interaction.